Photoacoustic measurement of thermal diffusivity of lasing dyes r6g incorporated in poly(methyl methacrylate)(pmma) and copolymer of methyl methacrylate(mma) with 2-hydroxyethyl methacrylate[p(mma:hema)] / Chan Kok Sheng, W. Mahmood Mat Yunus and Wan Md. Zin Wan Yunus - Chan, Kok Sheng; Mat Yunus, W. Mahmood; Wan Yunus, Wan Md. Zin (2002)
The application of photoacoustic technique was demonstrated for measuring the thermal diffusivity of R6G doped in solid matrix poly (methylrnethacrylate) (PMMA) and copolymer of methyl methacrylate(MMA) with 2-hydroxyethyl methacrylate(HEMA) [P(MMA:HEMA)]. The thermal diffusivity value obtained for R6G-doped PMMA is higher than the copolymer ofR6G-doped [P(MMA:HEMA)]. The optical spectra of the samples were measured by using a fibre optics spectrophotometer. The result shows that the R6G-doped [P(MMA:HEMA)] offers a good optical transmission and improved surface quality when compared to R6G-doped PMMA.